Querer ser, ser e deixar de ser coordenador pedagógico: um estudo sobre a rotatividade na função na rede municipal de ensino de Jundiaí - Pereira, Karina Stefanin (2018)
This study aims to identify the reasons of the turnover among the professionals who are in charge of the pedagogical coordination. Considering that, in many cities, the pedagogical coordinator takes over a function, instead of a permanent position, this research aimed to investigate the reasons that led the subjects to take over such function and why they resigned from it and returned to the position of teacher some time later. The research hypothesis is that the expectations of the professionals are not confirmed while working as a pedagogical coordinator and the difficulties they find to meet all the demands determine their resigning, which, comes to cause the turnover in the function. The main theoretical references mobilized were the studies on pedagogical coordination by Flávia Vieira, the concepts of schoolcentered in-service teacher training by João Barroso and Juan Manuel Escudero and Antonio Bolívar Botia and, fundamentally, the concept of turnover by Maria Helena Galvão Frem Dias da Silva and Cilene Ribeiro de Sá Leite Chakur. The research was developed in the municipal schools of Jundiaí, SP, through a scale questionnaire, answered online by professionals of Basic Education who resigned from the function of pedagogical coordinator between 2013 and 2016. The results show that the resignation of the function was determined by the fact that some expectations were not confirmed while developing the functional requirements, such as the desire to carry out the in-service teacher training, to contribute to the school improvement and to take part in a training program themselves; and also because of the difficulties they find, such as an increase in working hours, the limitation of work to solving conflicts and problems, and the feeling of solitude while working as a pedagogical coordination. In addition, the data indicate that the fact that pedagogical coordination is not an effective position influences the turnover of the function, since they take responsibility of it with the intention of doing it only for a short period of time